Colostrum Management: Keys to Optimizing Output and Uptake of Immunoglobulin G - Erickson, Peter S. (Frontiers in Animal Science, 2022)
Colostrum is essential for the health and well-being of dairy cattle. This review provides insight into different means of augmenting or enhancing colostrum quality including colostrum feeding, dry cow management, prepartum cow diets, freezing, pasteurization, colostrum additives, and colostrum replacers. Other components in colostrum such as maternal cells and their importance are discussed. New research is needed regarding the components in colostrum (bioactive peptides, and growth factors) and their effects on the neonate. Colostrum replacers and a prediction equation to estimate colostrum quality are reviewed.